Photovoice research with disabled girls of color: exposing how schools (re)produce inequities through school geographies and learning tools. Issue 8 (14th September 2022) - Miller, Amanda L.; Kurth, Jennifer A.
Abstract: Across the globe, disabled girls of color have unique school experiences and perspectives. However, they are often left out of educational research. In addition, their experiences are not included in conversations focused on transforming school systems and practices, even though they have solutions for educational equity and justice. Grounded in intersectionality and critical spatial theory, this study expands current understandings of how school systems and practices impact disabled youth of color broadly by considering the distinct intersectional educational trajectories of disabled girls of color in middle and high school in the United States. Through their counter-narratives, photographs, and maps, focal participants revealed how materializations (e.g. school geographies, learning tools) and adult actions impacted their academic and social opportunities at school. This study adds to the current literature with a purposeful focus on the experiences and solutions of disabled girls of color. Implications for research and practice are discussed. Points of interest: This article looks in detail at the experiences of disabled girls of color in the U.S. in one middle school and one high school. Disabled girls of color were often accompanied by adults throughout the school day. Few girls could travel to classrooms on their own or with friends or store personal materials in their own lockers. Disabled girls of color had limited access to many school spaces and classrooms. Most disabled girls of color did not have access to preferred writing tools (e.g. pencils, pens). Most girls had fewer math and science materials and electronic devices (e.g. laptops, tablets) to learn with compared to other students at their school. The researchers recommend teachers ask disabled girls of color about their experiences to ensure they have access to spaces and materials for meaningful learning. Teachers could use photography and map-making to learn about student experiences and modify their teaching practices.